Coke zero for the zero: A randomized controlled trial examining coke zero consumption on night call inpatient course and mortality - Yu Heng Kwan; Haoming Tang; Lihua Qi; Angela Frances Hui Wen Yap; Linxuan Yan; Yi Xin Li; Andrea Zhe Ern Lee; Antoinette Shui Wen Fong; Yarn Kit Chan; Feng Yi Low; Charmaine Wai Yan Sum; Benjamin Jun Jie Seng; et al. (Proceedings of Singapore Healthcare)
Background Coca-Cola and Cola-Cola Zero Sugar are commonly consumed beverages by healthcare professionals. Medical superstitions abound about whether Cola-Cola Zero sugar consumption affects night call outcomes. Objectives The current study aimed to determine whether Coca-Cola Zero Sugar, compared to regular Coca-Cola, is associated with any differences in inpatient admissions and mortality of patients on night calls. Methods A double-blinded randomized controlled trial was conducted in the Division of Medicine, Singapore General Hospital, Singapore involving junior doctors from January 2024 to February 2024.The primary outcome was the number of ward admissions under the night call doctor’s care. Secondary outcomes involved the number of inpatient deaths, high-dependency or intensive care admissions, the number of hours slept by the doctor, the number of steps walked by the doctor, and the level of sleepiness of the doctor on call. Results 203 participants consented and were randomized (44.9%). The data of 198 participants were included for analysis (97.5%). No significant differences were detected in the number of ward admissions between the Coca-Cola Zero Sugar group and the regular Coca-Cola group. For secondary outcomes, a significant difference was present between the two groups in the Karolinska Sleepiness Scale score ( p -value = .0413). Other secondary outcomes did not demonstrate significant differences between the two groups. Conclusions No convincing evidence was present to support the consumption of Coca-Cola Zero Sugar versus the regular Coca-Cola had significant differences in the number of inpatient admissions and mortality in night call duties.